(untitled) (Journal of Hama University, 2026)
This research aims to determine the relationship between E-Leadership and Intellectual Capital in Syria in the Ministry of Internal Trade and Consumer Protection (Aleppo Directorate). To achieve this objective, the researcher used a hypothetical-deductive approach to formulate the hypotheses. (85) questionnaires were distributed to the employees that are under study. (79) questionnaires were retrieved and (75) were valid for analysis. a statistical study was conducted to reveal this relationship. The researcher used the correlation coefficient (Person). The study concluded that there is a significant relationship between E-Leadership and Intellectual Capital in the Directorate of Domestic Trade and Consumer Protection in Aleppo. This study also reached a set of recommendations and proposals, Which Would Contribute Positively to Helping Maximizing Intellectual Capital in Public Sector Institutions.